From loyal british subjects to ardent revolutionaries anti-british political activities of the sikh in Malaya 1914-1945 - Ranjit Singh, Malhi (2015)
This historical study, adopting a thematic approach and utilizing both primary and secondary sources, examines the anti-British political activities of the Malayan Sikhs during the period 1914-45. It focuses on the involvement of Malayan Sikhs in the Ghadar movement (1913-18), the Komagata Maru incident of 1914, the Singapore Mutiny of 1915, the Akali movement (1920s), and the Indian independence movement (1942-45). The study reveals that numerous Malayan Sikhs were transformed from loyal British subjects into ardent revolutionaries primarily due to the influence of the virulent Ghadar propaganda, the brutal treatment of the British authorities in India against the returning passengers of the Komagata Maru, Jallianwala Bagh Massacre of 1919, and the Nankana Sahib Massacre of 1921. The various anti-British political activities of the Malayan Sikhs were geared towards either gaining independence for India or safeguarding the religio-political interests of the Sikh panth in India, particularly in the Punjab. The study contributes significantly to new knowledge by substantiating that the Ghadar and Akali movements were much more "alive and kicking" in Malaya than generally believed. Indeed, hundreds of Malayan Sikhs returned to India to take part in the planned 1915 Ghadar uprising against the British Raj and in the Akali morchas during the 1920s. It also sheds new light on the contributions of the Sikhs towards the Indian independence movement in Malaya. Additionally, the study revises and refines existing knowledge in a number of areas: it affirms that the Ghadarites played a much more significant role in the outbreak of the 1915 Singapore Mutiny than hitherto believed; the Mountain Battery of the Malay States Guides did not participate in the outrages of the 1915 Singapore Mutiny; and Gurdit Singh, the hero of the Komagata Maru incident, was a long-time resident of Serendah, Selangor and not that of Singapore or Hong Kong.